Visualizing nature's elegance: rice weevil morphology and their ecological significance - Azis, Tun Mohd Firdaus; Kasim, Khairul Farihan; Raja Omar, Raja Hanif Asyraf (2024)
Approximately 1,660 insect species have been reported to be associated with stored products during storage, processing, transportation and marketing (Hagstrum and Subramanyam 2009). Among these, genus Sitophilus comprises the most significant pests of stored product (Padmasri et al. 2017). Sitophilus granarius, Sitophilus oryzae and Sitophilus zeamais are the three species in genus Sitophilus that garnered considerable attention because of their status as pest in cereal crops such as wheat, corn, rice, and sorghum. While these three species share similar life history, they exhibit several differences in their seed exploitation strategies (Campbell 2002; Longstaff 1981). Two common insect species have been identified as major pests in stored rice in Malaysia. The rice weevil, S. oryzae is considered as the most prevalent pest across all types of rice stored in houses (Reza Khan and Kanti Halder 2012, Mariana 2009). Rice weevils demonstrate remarkable adaptability to various environmental conditions, making them a challenging pest to be controlled effectively. This adaptability underscores the need for ongoing research and pest management efforts to protect rice stocks and ensure food security (Dent, 2000).